Influence of SPION Surface Coating on Magnetic Properties and Theranostic Profile - Ferreira-Filho, Vital Cruvinel; Morais, Beatriz; Vieira, Bruno J. C.; Waerenborgh, João Carlos; Carmezim, Maria João; Tóth, Csilla Noémi; Même, Sandra; Lacerda, Sara; Jaque, Daniel; Sousa, Célia T.; Campello, Maria Paula Cabral; Pereira, Laura C. J. (Molecules (Basel, Switzerland), 2024)
This study aimed to develop multifunctional nanoplatforms for both cancer imaging and therapy using superparamagnetic iron oxide nanoparticles (SPIONs). Two distinct synthetic methods, reduction–precipitation (MR/P) and co-precipitation at controlled pH (MpH), were explored, including the assessment of the coating’s influence, namely dextran and gold, on their magnetic properties. These SPIONs were further functionalized with gadolinium to act as dual T1/T2 contrast agents for magnetic resonance imaging (MRI). Parameters such as size, stability, morphology, and magnetic behavior were evaluated by a detailed characterization analysis. To assess their efficacy in imaging and therapy, relaxivity and hyperthermia experiments were performed, respectively. The results revealed that both synthetic methods lead to SPIONs with similar average size, 9 nm. Mössbauer spectroscopy indicated that samples obtained from MR/P consist of approximately 11–13% of Fe present in magnetite, while samples obtained from MpH have higher contents of 33–45%. Despite coating and functionalization, all samples exhibited superparamagnetic behavior at room temperature. Hyperthermia experiments showed increased SAR values with higher magnetic field intensity and frequency. Moreover, the relaxivity studies suggested potential dual T1/T2 contrast agent capabilities for the coated SPpH-Dx-Au-Gd sample, thus demonstrating its potential in cancer diagnosis.